ルベーグ積分の基本性質

ルベーグ積分の線形性

Statement

$E,F \in \mathcal{M}, E \cap F = \emptyset$
$f \in \mathcal{L}$ then $$ \int_{E \cup F} f dm = \int_E fdm + \int_F fdm $$

Proof

Statement

* ルベーグ積分は、$\mathcal{L}$ 上の線形汎関数である. つまり (i) $f \in \mathcal{L}, a \in \mathbb{R} \Rightarrow \int af dm = a \int f dm$
(ii) $f, g \in \mathcal{L} \Rightarrow \int (f + g) dm = \int f dm + \int g dm$

Proof

(i) $\{s^{(i)}(x)\}$:単関数列 such that $$ \lim_{i \rightarrow \infty} s^{}(x) = f(x)\\ s^{(i)}(x) = \sum_{j=1}^{k^{(i)}} s_j^{(i)} \cdot \chi_{E_j^{(i)}}(x) $$ then
$\lim_{i \rightarrow \infty} as^{(i)}(x) = af(x)$.
therefore $$ \int afdm = \lim_{i \rightarrow \infty} \sum_{j=1}^{k^{(i)}} a s^{(i)}_j m(E_j^{(i)}) \\ = \lim_{i \rightarrow \infty} a \sum_{j=1}^{k^{(i)}} s^{(i)}_j m(E_j^{(i)}) \\ = a \lim_{i \rightarrow \infty} \sum_{j=1}^{k^{(i)}} s^{(i)}_j m(E_j^{(i)}) \\ = a \int fdm $$ (ii) (1) $f \ge 0, g \ge 0$
(2) $f \lt 0, g \lt 0$
(3) $f \ge 0, g \lt 0, f + g \ge 0$
(4) $f \ge 0, g \lt 0, f + g \lt 0$
(5) $f \lt 0, g \ge 0, f + g \ge 0$
(6) $f \lt 0, g \ge 0, f + g \lt 0$
(1) $$ \int (f + g) dm = \lim_{i \rightarrow \infty} \sum_{j=1,l=1}^{j=k^{(i)},l=m^(i)} (s^{(i)}_j + t^{})m(E_j^{(i)} \cap F_l^{(i)}) \\ = \lim_{i \rightarrow \infty} \{ \sum_{j=1,l=1}^{j=k^{(i)},l=m^(i)} s^{(i)}_jm(E_j^{(i)} \cap F_l^{(i)}) + \sum_{j=1,l=1}^{j=k^{(i)},l=m^(i)} t^{}m(E_j^{(i)} \cap F_l^{(i)}) \} \\ = \lim_{i \rightarrow \infty} \{\sum_{j=1}^{j=k^{(i)}} s^{(i)}_jm(E_j^{(i)}) + \sum_{l=1}^{l=m^(i)} t^{}m(F_l^{(i)}) \} \\ = \lim_{i \rightarrow \infty} \sum_{j=1}^{j=k^{(i)}} s^{(i)}_jm(E_j^{(i)}) + \lim_{i \rightarrow \infty} \sum_{l=1}^{l=m^(i)} t^{}m(F_l^{(i)}) \\ = \int f dm + \int g dm \\ $$ (2) $$ \int (f + g) dm = \int -1 \cdot -1 (f + g) dm \\ = - \int (-f + -g) dm \\ = - (\int -f dm + \int -g dm) \\ = - (-\int f dm + -\int g dm) \\ = \int f dm + \int g dm \\ $$ (3) $$ \int f dm = \int (f + g - g) dm \\ = \int (f + g) dm + \int - g dm \\ = \int (f + g) dm - \int g dm \\ \therefore \int (f + g) dm = \int f dm + \int g dm \\ $$ (4) $$ \int -f dm = \int (-f - g + g) dm \\ = \int -(f + g) dm + \int g dm \\ = - \int (f + g) dm + \int g dm \\ \therefore \int (f + g) dm = \int f dm + \int g dm \\ $$ (5),(6) 略.

Statement

* $\mathcal{L}$ は $\mathbb{C}$ 上のベクトル空間である.

Proof